Dynamic integration paths of emerging multinational enterprises in advanced markets: Empirical evidence from Chinese acquisitions in Germany. Issue 1 (5th December 2019) - Yang, Yanan; Lütge, Christoph
Abstract : Purpose: This paper aims to examine dynamic multi-stage post-merger integration (PMI) evolutions by Chinese multinational enterprises (CMNEs) in the German market and their potential influencing factors. Design/methodology/approach: A data set was collected from 25 interviews with 21 respondents from six Chinese acquisition cases in Germany, and a comparative multi-case study and content analysis were applied. Findings: The results reveal that Chinese acquirers take segmented linear integration path in Germany from nearly no integration to organisational integration and then to production integration. It contains three sub-paths: the P-O-O path (partnering–organisational optimisation–production optimisation), the P-P-P path (preservation–organisational preservation–production preservation) and the P-C-C path (preservation–organisational centralisation–production confusion). The initial nearly no integration condition is mainly impacted by asymmetric information and the targets' strategic positions, whereas different organisational and production integration degrees in mid- and long-term stages are primarily influenced by Chinese acquirers' different dynamic capabilities. Moreover, Chinese acquirers' corporate ownership is not found to be a significant factor that influences CMNEs to take different integration strategies in different PMI stages. Research limitations/implications: This paper contributes to broaden emerging multinational enterprises' (EMNEs) PMI theory by adding dynamic perspective and provides suggestions for mergers and acquisitions (M&As) practitioners to identify integration options and avoid integration pitfalls in different integration stages. Originality/value: Existing works identified that EMNEs prefer to partner with the targets in advanced markets, but lacked a dynamic perspective to disclose whether the partnering strategy would be adjusted or not over time. This study is the first to explore multi-stage integration changes and is one of the few studies that recognise the interaction of the integration strategy with the dynamic capability of the acquiring enterprises.